2017
DOI: 10.3389/fimmu.2017.00903
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma Infection Favors Brucella Elimination via IL-12/IFNγ-Dependent Pathways

Abstract: This study develops an original co-infection model in mice using Brucella melitensis, the most frequent cause of human brucellosis, and Trypanosoma brucei, the agent of African trypanosomiasis. Although the immunosuppressive effects of T. brucei in natural hosts and mice models are well established, we observed that the injection of T. brucei in mice chronically infected with B. melitensis induces a drastic reduction in the number of B. melitensis in the spleen, the main reservoir of the infection. Similar res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…This may be the consequence of the higher number of CD4 + T cells in absence of CD8 + T cell in TAP1 −/− mice. In a previous study (47), we demonstrated that even though the amounts of IFN-γ produced by CD8 + T cells and CD4 + T cells are similar, CD8 + T cells are unable to replace CD4 + T cells in their control of Brucella infection, suggesting that CD4 + T cells deploy as yet unidentified effector mechanisms that may be independent of IFN-γ. In the i.d.…”
Section: Resultsmentioning
confidence: 74%
“…This may be the consequence of the higher number of CD4 + T cells in absence of CD8 + T cell in TAP1 −/− mice. In a previous study (47), we demonstrated that even though the amounts of IFN-γ produced by CD8 + T cells and CD4 + T cells are similar, CD8 + T cells are unable to replace CD4 + T cells in their control of Brucella infection, suggesting that CD4 + T cells deploy as yet unidentified effector mechanisms that may be independent of IFN-γ. In the i.d.…”
Section: Resultsmentioning
confidence: 74%
“…This suggests that the strong pro-inflammatory IFNγ-mediated immune response induced by the T. brucei infection aided the clearance of Brucella . Thus, although infections with T. brucei can induce significant levels of immunosuppression and immunopathology, this study shows that under some circumstances the host's response to T. brucei infection may provide protection against co-infection with other pathogens ( 41 ). However, this not true for all pathogenic bacteria.…”
Section: Trypanosomesmentioning
confidence: 85%
“…Trypanosome infections may also modulate host susceptibility to infection with some pathogenic bacteria. For example, in mice chronically-infected with either Brucella melitensis, B. abortus , or B. suis , the burden of bacteria in the spleen was reduced if the mice were also co-infected with T. brucei ( 41 ). The effects of T. brucei infection on Brucella burdens in co-infected mice were impeded in the absence of functional IL-12p35/IFNγ signaling.…”
Section: Trypanosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed recently ( 87 ) that the strong Th1 response induced by Trypanosoma brucei infection significantly reduced Brucella growth but did not affect the course of M. tuberculosis infection in mice. Taken together, the absence of an impact of the Th1 response induced by T. brucei and the Th2 response induced by asthmatic sensitization on M. tuberculosis infection in our mice models is very surprising and suggests that control of M. tuberculosis is not simply dependent on a balance between the Th1 and Th2 responses.…”
Section: Discussionmentioning
confidence: 90%